International Joint- and Double-Degree Programs - Obst, Daniel; Kuder, Matthias (International Higher Education, 2012)
In response to the recent growth of joint and double degree programs over the past two decades, the Institute of International Education and Freie Universität Berlin conducted an international survey that assessed the challenges, opportunities, motivations, and impact of developing collaborative degree programs from a global perspective.